Sustainable Local Development Potential of the Elaphites, Croatia - Anamarija Pisarovic\'; Iva Tolic\'; Sanja Tisma (ENTRENOVA - ENTerprise REsearch InNOVAtion, 2022)
The Elaphites comprise the archipelago of 13 islands, among them eight larger and five smaller stretching northwest of Dubrovnik in the Adriatic sea. The islands are covered with characteristic Mediterranean evergreen vegetation and attract large numbers of tourists during the summer due to their beaches and pristine nature. Only the three main islands are permanently inhabited, supporting a modest tourist industry. The diffuse hotel model ("Albergo Diffuso") is defined as creating visitor accommodation by reusing and restructuring existing houses, which must be located within an inhabited town center and therefore has multifold economic, social and environmental benefits for local communities. The core of the scattered hotel concept envisages its interaction with small village communities. The paper analyzes the socio-economic and environmental characteristics of this innovative approach to enhancing tourism activities and restoring the valuable cultural, natural, and historical heritage of the Elaphites.
Keywords: O13; 330; The Elaphites; diffuse hotel concept; sustainable tourism; cost-benefit analysis; risk analysis